(untitled) (Bulletin of criminological association of Ukraine, 2025)
The article is devoted to the problem of various definitions of the concept of «secret» contained in national legislation and scientific legal literature, the article examines existing approaches to the legal regulation of this phenomenon. Using general scientific methods of analysis and synthesis, it is established that the legislatively defined cases of restriction of access to «information» are aimed at ensuring the socially useful function of regulating relations in order to prevent harm from the disclosure of certain information. The absence of a single regulatory legal act that would establish a list of all varieties of «secrets» is noted, and the essence of the reasons that complicate the classification of «secrets» is also emphasized. The conclusion is made about the inexpediency of codifying the relevant legal norms at the current stage of development of national legislation. The use of incorporation (based on the main features of the «secret» category) as an approach, the results of which can be effectively used in the processes of education, training and rulemaking, is proposed.